Black Friday and Cyber Monday: understanding consumer intentions on two major shopping days - Swilley, Esther L.; Goldsmith, Ronald E. (My University, 2013)
U.S. Retailers consider two major holiday shopping days as their most profitable—the Friday after Thanksgiving, Black Friday, and the Monday after Thanksgiving, Cyber Monday. Understanding consumer attitudes and intentions toward shopping in the mall or online at these times may aid retailers in their holiday marketing activities. This study uses data from a survey of 225 U.S. consumers to examine attitudes and behaviors of shoppers for these two shopping occasions. The results indicate that consumers enjoy shopping on Black Friday, yet were more likely to shop on Cyber Monday owing to its greater convenience. Retail managers will have a better opportunity to market on these two days with an understanding of consumer intentions for these major shopping occasions based on these findings.
Keywords: Online shopping; Black Friday; Cyber Monday